Alexithymia and anxiety symptoms in Pakistani adolescents: a study of compounded directions - Sadia jafer; Farzana Ashraf; Amna Arif (Journal of the Pakistan Medical Association, 2021)
Objectives: There is an empirical evidence that symptoms of internalizing disorders such as alexithymia and anxiety increase in adolescence and these symptoms varies across gender and age groups. The purpose of this study was to explore these differences in adolescents. Method: In this cross-sectional study conducted since November 2018 to March 2019, the sample of 185 adolescents selected through random sampling method from different schools. They were assessed on alexithymia and anxiety symptoms by administering Toronto Alexithymia Scale and Hamilton Anxiety Scale respectively. Multiple Analysis of Variance (MANOVA) was applied to determine the direct and interactive effect of age groups and gender on alexithymia and anxiety symptoms. Results: The results demonstrate that boys reported significantly (p<0.05) higher level of alexithymia symptoms partially (externally oriented) as compared to their counterparts. Further significant (p<0.05) interactive effect of age group and gender was also seen. Conclusion: The present study concluded that the presence of clinical symptoms in school going adolescents may hinder in the physical and psychological health of adolescents, which should be managed through suitable interventions. Keywords: Alexithymia symptoms, Anxiety symptoms, Continuous...